PENGARUH MOTIVASI KERJA, DISIPLIN KERJA DAN KOMPENSASI TERHADAP KINERJA PEGAWAI PADA DINAS PERINDUSTRIAN DAN PERDAGANGAN KOTA DEPOK - Sri Lestari (STIKOM CKI, 2017)
The purpose of this research is to know the influence of work motivation, work discipline, and compensation to good employee performance simultaneously and partial also to know dominant variable that influence the employee performance. Department of Industry and Commerce Depok is the researcher location with 40 employees as respondent. Data analysis techniques used to test the hypothesis are multiple linear regressions analysis that has a purpose to know the simultaneous and partial influences also to determine the dominant variable that influences employee performance. Based on the analysis result we know that work motivation variable, work discipline, and compensation positive influences and significant simultaneously to industry and commerce department of depok employee performance city. Work motivation variable, Work discipline, and compensation has positive influences partially to employee performance at the department of industry and commerce of depok with Work discipline variable as the most influence variable to employee performance. Keywords : work motivation, work discipline, compensation, employee performance.